2005
DOI: 10.1021/jm0508890
|View full text |Cite
|
Sign up to set email alerts
|

HIV Integrase Inhibitors with Nucleobase Scaffolds:  Discovery of a Highly Potent Anti-HIV Agent

Abstract: HIV integrase is essential for HIV replication. However, there are currently no integrase inhibitors in clinical use for AIDS. We have discovered a conceptually new β-diketo acid that is a powerful inhibitor of both the 3′-processing and strand transfer steps of HIV-1 integrase. The in vitro anti-HIV data of this inhibitor were remarkable as exemplified by its highly potent antiviral therapeutic efficacy against HIV TEKI and HIV-1 NL4-3 replication in PBMC (TI >4,000 and >10,000, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…56 Figure 15) [112,120] were cytotoxic. In keeping with the indole DKAs, purine (57 & 58, Figure 16) 121 and pyrimidine (59 & 60) [122] analogues displayed potent in vitro activity, reduced in vivo activity and reduced strand-transfer selectivity. However, the reduction of selectivity of these analogues is not expected as they mimic the natural substrate.…”
Section: Polyhydroxylated Aromatic Hiv-1 Inhibitorsmentioning
confidence: 69%
“…56 Figure 15) [112,120] were cytotoxic. In keeping with the indole DKAs, purine (57 & 58, Figure 16) 121 and pyrimidine (59 & 60) [122] analogues displayed potent in vitro activity, reduced in vivo activity and reduced strand-transfer selectivity. However, the reduction of selectivity of these analogues is not expected as they mimic the natural substrate.…”
Section: Polyhydroxylated Aromatic Hiv-1 Inhibitorsmentioning
confidence: 69%
“…In our laboratory, we discovered conceptually new -diketo acids with nucleobase scaffolds that are potent inhibitors of both the 3 0 P and ST steps of HIV integrase [63][64][65][66][67]. Our data suggest that the nucleobase scaffold, the substituents and the specific spatial relationship of substituents in the scaffold, are critical for potent integrase inhibitory activity.…”
Section: Diketo Acids With Nucleobase Scaffoldsmentioning
confidence: 90%
“…Nair et al reported that bis-benzylated nucleobase with a -diketo acids are potent HIV integrase inhibitors [12].…”
Section: Introductionmentioning
confidence: 99%